REVERSAL OF HALOFANTRINE RESISTANCE IN PLASMODIUM FALCIPARUM BY PENFLURIDOL IN VITRO - M. Nateghpour; R.E. Howells; S.A. Ward (Tehran University of Medical Sciences, 1998)
Penfluridol, a neuroleptic drug, considerably reversed halofantrine resistance in T9.96HF halofantrine resistant strain of Plasmodium falicparum (originally chloroquine sensitive parasites), but not in K1HF halofantrine resistant strain (originally chloroquine resistant parasites)